Has the Impact of Rising CO2 on Plants been Exaggerated by Meta-Analysis of Free Air CO2 Enrichment Studies? - Haworth, Matthew; Hoshika, Yasutomo; Killi, Dilek (Frontiers in Plant Science, 2016)
Meta-analysis is extensively used to synthesise the results of free air CO2 enrichment (FACE) studies to produce an average effect size, which is then used to model likely plant response to rising [CO2]. The efficacy of meta-analysis is reliant upon the use of data that characterises the range of responses to a given factor. Previous meta-analyses of the effect of FACE on plants have not incorporated the potential impact of reporting bias in skewing data. By replicating the methodology of these meta-analytic studies, we demonstrate that meta-analysis of FACE has likely exaggerated the effect size of elevated [CO2] on plants by 20 to 40%; having significant implications for predictions of food security and vegetation response to climate change. Incorporation of the impact of reporting bias did not affect the significance or the direction of the [CO2] effect.